Do You Wish to Prosecute the Person Who Assaulted You?: Untested Sexual Assault Kits and Victim Notification of Rape Survivors Assaulted as Adolescents. Issue 5 (4th July 2018) - Feeney, Hannah; Campbell, Rebecca; Cain, Debi
ABSTRACT: In jurisdictions across the country, sexual assault kits (SAKs) have not been consistently submitted for testing and many cities are now submitting large quantities of SAKs for forensic DNA testing. As a result, some survivors will be asked to re-engage with the criminal justice system, a process that may raise complex issues for victims who were adolescents at the time of their assaults. The authors examine the experiences of 15 adolescent victims whose SAKs were not tested, and their decision-making pathways regarding reengagement with the criminal justice system years after the initial investigation. Findings reveal that characteristics of the initial assault, victim-blaming experiences, and the social support appear to be related to the decision to re-engage with law enforcement years after the initial assault. Implications for future research and practice are discussed.